Uncertainty of the Linear Trend in the Zonal SST Gradient Across the Equatorial Pacific Since 1881. Issue 1 (1st January 2019) - Zhang, Chan; Lian, Tao; Tang, Youmin; Ying, Jun; Li, Junde
ABSTRACT: The change in the zonal sea surface temperature gradient (ZSSTG) across the equatorial Pacific plays an important role in the global climate system. However, there has not yet been a consensual conclusion about the changing ZSSTG at either a short-term (from 20 to 90 years) or a long-term time scale (longer than 90 years) in the literature. In this study, the uncertainty of the trend in ZSSTG for different sub-periods since 1881 was examined using four interpolated datasets and four un-interpolated datasets. It was found that the trend in ZSSTG on the short-term time scale could be significantly influenced by internal variability such as the El Niño–Southern Oscillation and the Pacific Decadal Oscillation. On the long-term time scale, the sign of the ZSSTG trend depends on the dataset used. In particular, it was not possible to draw a uniform conclusion about the secular trends in ZSSTG in recent history, given the high sensitivity of the ZSSTG trends to the period, dataset, and regions used to calculate the trends. Our results imply that it may not be possible to detect the response of ZSSTG to global warming until a longer data record becomes available in the future.